Karakteristik Fisik dan Aktivitas Antioksidan Sediaan Masker Gel Peel Off Ekstrak Metanol Daun Eceng Gondok: Physical Characteristics Gel Peel Off Mask from Methanol Crude Extracts of Water Hyacinths - Nabila Ukhty; Ikhsanul Khairi; Tika Wulan Dari (Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2022)
Gel peel off face mask is one type of facial mask that can increase the comfort of use and is expected to increase antioxidant activity on the skin. The mask is shaped like a paste, with a thick texture. Water hyacinths (Eichhornia crassipes) is an aquatic plant that lives wild in the waters of West Aceh. The purpose of this study was to determine the yield of methanolic crude extract of water hyacinths’s leaves and to find out the best formulation of gel peel off face mask from methanol crude extract of water hyacinths’s leaf based on the physical characteristics of the mask. The extraction method used was maceration using methanol as a solvent. The differences in the composition of the extracts used were concentrations of 0%, 2%, 4% and 6%. Exploration of bioactive compounds in crude extract using phytochemical test. Assessment of the physical characteristics of the mask preparation included organoleptic tests, homogeneity, adhesion, dispersibility, pH, and drying time. The crude extract contains flavonoid compounds, tannins, steroids, terpenoids, and saponins. Formulation 3 for making gel peel off masks was the best mask with an assessment of its homogeneity being stable and no change, adhesion for 5.30 seconds, dispersion of 5.9 cm, pH 6.4, and drying in 27.48 minutes. The formula has DPPH inhibition (% inhibition) of 76.54%.